A Hospital-based study on the application of blockchain technology on data sharing in oncology treatment and value-based care in Nairobi County, Kenya - Saini, B. V. (Strathmore University, 2023)
This study deals with the Blockchain Technology (BcT) application for decentralizing Electronic Health Records (EHRs) data to store patient information, including medical reports, to ensure improved patient care. EHRs are entirely controlled by hospitals instead of patients, which makes it more difficult for patients to seek medical care from other providers using their historical data. Patients are the data subjects and the primary owners of the data; therefore, they should have more say and checks on balances on the providers in how their data is being shared and used. The existing system of storing patient details depends on the organization's servers, thus the need for Blockchain using multi-cloud integration to achieve data interoperability. This study will adopt a quantitative research design whereby Blockchain will design an experiment to establish the relationship between patient perspective, level of trust, and transparency in data sharing for oncology patients and value-based care through processing and analyzing the quantitative data from the private cancer center. This study will adopt a quantitative with various stakeholders in Oncology in Kenya. It will also undertake surveys through questionnaires with the chief oncologist, chief medical officer, nurse manager, lab technician, researchers, and IT personnel. The results showed that blockchain technology has the potential to transform the way health records and data are kept and used to treat and care for oncology patients. By combining and integrating data from various sources, healthcare organizations can enhance value-based care, prioritizing patient outcomes and using data to drive decision-making. Furthermore, evidence-based decision-making by extracting data insights is important for designing data-driven healthcare systems. This study provides valuable insights for healthcare policymakers, providers, and researchers in Kenya and beyond. By prioritizing patient outcomes, evidence-based decision-making, and data protection, healthcare organizations can improve the quality of care they provide and, ultimately, the health outcomes of their patients. Furthermore, by leveraging blockchain technology and other innovative solutions, healthcare providers can improve their services' efficiency, effectiveness, and sustainability.
Full - text thesis